The impact of monetary incentives on general fertility rates in Western Australia - Langridge, A.; Nassar, N.; Li, Jianghong; Jacoby, P.; Stanley, F. (BMJ Publishing, 2012)
Background: There has been widespread international concern about declining fertility rates and the long-term negative consequences particularly for industrialised countries with ageing populations. In an attempt to boost fertility rates, the Australian Government introduced a maternity payment known as the Baby Bonus. However, major concerns have been raised that such monetary incentives would attract teenagers and socially disadvantaged groups. Methods: Population-level data and generalised linear models were used to examine general fertility rates between 1995 and 2006 by socioeconomic group, maternal age group, Aboriginality and location in Western Australia prior to and following the introduction of the Baby Bonus in July 2004.Results: After a steady decline in general fertility rates between 1995 and 2004, rates increased significantly from 52.2 births per 1000 women, aged between 15 and 49 years, in 2004 to 58.6 births per 1000 women in 2006. While there was an overall increase in general fertility rates after adjusting for maternal socio-demographic characteristics, there were no significant differences among maternal age groups (p=0.98), between Aboriginal and non-Aboriginal women(p=0.80), maternal residential locations (p=0.98) or socioeconomic groups (p=0.68). The greatest increase in births were among women residing in the highest socioeconomic areas who had the lowest general fertility rate in 2004 (21.5 births per 1000 women) but the highest in 2006 (38.1 births per 1000 women). Conclusions: Findings suggest that for countries with similar social, economic and political climates to Australia, a monetary incentive may provide a satisfactory solution to declining general fertility rates.